2008
DOI: 10.1002/gps.1977
|View full text |Cite
|
Sign up to set email alerts
|

What do we know about dementia?: a survey on knowledge about dementia in the general public of Japan

Abstract: There appeared to be gaps in knowledge on dementia among the general public, which may prevent caregivers from planning upcoming social and financial challenges. Correct information needs to be given by health professionals and care staff. Educational initiatives planned for the general public could be useful, and should target those groups, men and non-middle aged women who have lower knowledge.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
85
1
3

Year Published

2008
2008
2011
2011

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 83 publications
(99 citation statements)
references
References 16 publications
(30 reference statements)
10
85
1
3
Order By: Relevance
“…Sanders (2005) also found rewards in AD caregivers who gained in spiritual growth, personal growth, and feelings of mastery. Satisfaction was also found in many studies of AD caregivers (Arai, Arai, & Zarit, 2008;Habermann & Davis, 2005) and was found to be positively correlated with a satisfactory relationship before the illness and quality of family functioning, and negatively correlated with burden (Andren & Elmstahl, 2005;Steadman, Tremont, & Davis, 2007). The theme "more public sensitization about AD" was extracted from many interviews.…”
Section: Discussionmentioning
confidence: 93%
“…Sanders (2005) also found rewards in AD caregivers who gained in spiritual growth, personal growth, and feelings of mastery. Satisfaction was also found in many studies of AD caregivers (Arai, Arai, & Zarit, 2008;Habermann & Davis, 2005) and was found to be positively correlated with a satisfactory relationship before the illness and quality of family functioning, and negatively correlated with burden (Andren & Elmstahl, 2005;Steadman, Tremont, & Davis, 2007). The theme "more public sensitization about AD" was extracted from many interviews.…”
Section: Discussionmentioning
confidence: 93%
“…The prevalence of dementia in Australia is predicted to rise significantly as the proportion of older people in the population increases, and by the year 2016 it is expected to be the major cause of disability in Australia (Australian Institute of Health and Welfare, 2006). To date, very few studies have investigated the general public awareness of dementia (Steckenrider, 1993;Werner, 2003;Arai et al, 2008) and only a small proportion of these studies have been conducted in Australia (Sullivan et al, 2003;Low and Anstey, 2007;Sullivan, 2008). Fewer studies have included samples from different nationalities or cultural groups (Ayalon and Arean, 2004;Purandare et al, 2007;Arai et al, 2008).…”
Section: Introductionmentioning
confidence: 95%
“…The ADK items include questions on general and biomedical information about Alzheimer's Disease (AD). Findings from such studies indicated poor levels of AD knowledge exist within the general community (Laforce and McLean, 2005;Arai et al, 2008;Sullivan, 2008). Sullivan et al (2007) modified the ADK for use in an Australian context.…”
Section: Introductionmentioning
confidence: 96%
See 2 more Smart Citations